Perspektiven einer Zeitschrift am Beispiel des Tirnauer Wochenblatts (1869–1918) - Unterer, Bernhard; Lipavic Oštir, Alja; Braxatorisová, Anita (University of Maribor Press, 2025)
Perspectives of a Magazine Using the Example of the Tirnau Wochenblatt (1869 – 1918). The monograph offers various linguistic analyses of texts from the German-Hungarian newspaper Tirnauer Wochenblatt (1869–1918), with a focus on issues published shortly before the turn of the century. This temporal focus can be explained by language policy and the emergence of vernacular nationalism — both in Tyrnau, located in present-day Slovakia and the place of publication of the newspaper, and in the broader context of the monarchy, a time in which a strengthened bourgeoisie, as the target readership of the weekly, played a central social role. The Tirnauer Wochenblatt is examined from different perspectives: both in terms of its internal structure and its role in its contemporary context. The analyses place the newspaper partly within the context of the German-speaking minority and the German-language press in Slovakia at that time. The first part investigates the extent to which, and the ways in which, the newspaper reflects the educational discourses of the period, presents family role models, and addresses gender-specific models of roles in family and society. In this context, the monograph conducts a series of exemplary qualitative analyses that incorporate the perspective of the value system of bourgeois society. The second part analyzes a section of the newspaper that presents news from various regions of the monarchy. From the perspective of the development of text types in the press of the 19th century, the text type news report is examined, and the corpus of news items is subsequently analyzed quantitatively according to ten different parameters. This is followed by a comparison with texts from the same section that provide information from around the world, as well as a fractal analysis of the texts themselves. The investigation is further complemented by a comparison with texts of the same function from the same period in the Marburger Zeitung (1862–1945). The third part of the monograph presents a corpus-based analysis of ethnonyms that appeared in the Hungarian supplement of the same newspaper. These ethnonyms not only reflect the political tensions of that period in the monarchy but also linguistically shape a consistent system of values and interpretations that opens up a perspective on the national and cultural dynamics of the region and the time.